School Based 4-H Programming: Incorporating Family Engagement into Your Program - Vanessa Spero (EDIS)
Family engagement in 4-H programs allows family members, youth, and the community to become more aware, cohesive, and invested in youth development. This 4-page fact sheet, written by Vanessa Spero-Swingle and published by the UF/IFAS Florida 4-H Youth Development Program, discusses how to incorporate family engagement into your 4-H school programming. For the purposes of Florida 4-H, a school-based program can be defined as school enrichment (offered to groups of youth, taught by Extension staff or trained volunteers, and designed to support the school curriculum), an in-school club following a more traditional club approach during school hours, or an after-school club operating directly after school hours. https://edis.ifas.ufl.edu/4h401